Poverty in South Africa: Drivers of Perpetuation - Faluyi, Olumuyiwa Temitope; Olutola, Adewale Adisa (African Journal of Inter/Multidisciplinary Studies, 2024)
Poverty remains a persistent issue within the socio-political landscapes of Africa. This study explores the income, food, and multidimensional nature of poverty in South Africa. The study found that economic, social, and political factors are not only responsible for poverty, but they perpetuate poverty in South Africa. These factors include weak institutions, unemployment, service delivery issues, corruption, security challenges and dysfunctional family settings. The study adopted the state fragility theory to demonstrate how weaknesses in state institutions affect their ability to discharge their functions as expected and how they manage the dynamics associated with these expectations. The study utilised the qualitative research method based on literature search from secondary sources. These included journal articles, books, institutional documents, and newspaper articles. Data were descriptively analysed. The study recommends strong state institutions to coordinate stemming the threat these poverty drivers pose to the well-being of South Africans. It also recommends commitment through good values demonstrated by the political class, bureaucracies, and the citizens.